Relationship between national private vehicle ownership, urbanization and economic growth - Chu, May Yen (2020)
National private vehicle (motorcycle and car) ownership varies among countries, cities and geographical regions but is strongly related to per capita income at different levels. During the early stages of economic development, the mode of transport is mainly motorcycles. As the countries’ economy grows, due to safety, convenience and comfort, car demand increases. However, factors such as urbanization and price level greatly affecting the choice of travel mode. Three empirical investigations were conducted and the research objectives are as follows: (i) to evaluate the relationship between urbanization, price and income level on motorcycle ownership and the effects of interactions between these factors, (ii) to determine the effect of urbanization, inflation and income level on car ownership and the effects of interactions between these factors and (iii) to assess the relative growth in motorcycle ownership as compared to the growth in private car ownership and per capita income. To shed light on the above issues, the negative binomial technique was used for the first objective to analyse on a panel of 73 countries over a period of 51 years, from 1963 to 2013. However, for the second objective, the Gompertz model was applied to analyse on a panel of 73 countries between 1963 and 2013. Finally, panel linear regression analysis was conducted for the third study using time-series cross-sectional data of 76 countries between 1963 and 2013. The first empirical study was to assess the effect of urbanization, price and per capita income on motorcycle ownership and the effects of interactions between these factors. Results indicated an inverse U-shaped relationship between the price level and motorcycle ownership. The estimated turning point of the inverse U-shaped relationship was found to increase with a rise in urbanization level. This inverse Ushaped relationship turned into U-shaped at a higher urbanization level. The results also confirmed the motorcycle-Kutznets relationship with per capita income and suggested that the inverse U-shaped varied with both price level and urbanization. The turning point decreased with increased urbanization under low price level, whereas the turning point increased with increasing urbanization under high price level. The second study reports the results of an empirical analysis of an S-curve relationship between car ownership and per capita income. Rapid urbanization induces car ownership, but the deterioration of purchasing power during high inflation may suppress this effect. Thus, the impact of urbanization on car ownership may vary across different inflation rates. This study aimed to examine the effects of urbanization and inflation on the S-shaped curve relationship between car ownership and per capita income. The results indicated that car ownership showed relatively greater elasticity to per capita income under high urbanization levels and low inflation rates. The evidence presented in this study suggests that car ownership reaches a higher saturation level under higher than lower urbanization. The third empirical study examined the relative growth of motorcycles to the relative growth of cars with per capita income. The estimated result pointed to an inverse U-shaped relationship between the relative growth of motorcycles to the relative growth of cars with the per capita income. The underlying factors that contributed to this relationship were urbanization, price level and road density. The impact of the price level and road density on the relative growth of motorcycles to the relative growth of cars was estimated to be positive at all per capita income levels, whereas negative for urbanization in accordance with increases in the per capita income. The key finding of this study indicates that before the threshold point of per capita income the relative growth in motorcycle ownership is greater while the relative growth in car ownership is greater after the threshold.